The Potential For Double Jeopardy Violations In The Regulation of The Imposition of Cumulation Of External Sanctions For Violations Of Space Utilization - Putri, Clarisa Permata Hariono; Rini, Wafia Silvi Dhesinta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Spatial planning provisions regulate the cumulative external sanctions for acts of violation of space use. This article aims to analyze potential violations of the double jeopardy principle of these provisions. This research is important considering that spatial planning plays an important role in realizing the welfare of the Indonesian people by the mandate of the state constitution so that law enforcement must be implemented appropriately without violating legal principles. The research results show that there is indeed a potential violation of the double jeopardy principle in the regulation, due to the developments of administrative and criminal sanctions nature. To overcome this, it’s necessary to reformulate the legal provisions of spatial planning and implement a cumulation of external sanctions that give more attention to legal principles.